Positive and negative effects of prior knowledge on referee decisions in sports - Plessner, Henning (The routines of decision making, 2005)
Referees1 are involved in most competitive sports; moreover, in some - sports, the assessment of athletes’ performance depends exclusively on human judgments. The tasks of referees vary from simple judgments to complex decisions. Many of these tasks surpass the limited human capacity to - process information (e.g., Salmela, 1978). For example, given the speed of - the modern tennis game, the human perceptual system does not allow for - differentiating between a ball that is on the line and one close to it - (Jendrusch, 2002). It lacks the appropriate temporal resolution. However, - decisions have to be made by referees even when situations are ambiguous - or unclear, or when important information is missing due to personal or situational factors. Such situations seem to occur quite often in sport competitions. For example, in a recent study on the influence of crowd noise on referee decision in soccer, Nevill, Balmer, and Williams (2002) asked referees - to make assessments for 47 typical incidents taken from an English Premier - League match. One of the findings was that none of these challenges resulted in a unanimous decision by all qualified referees participating in the - study (see also Rainey, Larsen, Stephenson, & Coursey, 1989). Additionally, - referees not only have to make decisions about situations, but also have to - evaluate the performance of other people, and there is always some inter-A P T E RHenning Plessner - University of Heidelberg1 1Depending on sports and specific tasks, referees are also called umpires, officials, linesmen, - judges, and others. In this chapter, the term referee refers to the general category of people who - monitor and control the application of the rules in a sporting competition.
Gesehen am 27.07.2022